Futebol: a geometria analítica no campo - Pereira, Ana Paula Lorenço (2013)
This paper presents a practical math approach to everyday math student through the measures used in the football field do teach analytical geometry to students from public high schools. The activities were developed in E. E. Nelson Fernandes, in the city of Santa Rita do Passa Quatro, where the autor of the study has taught for 20 years and it was found that there is a mechanization of using standard formulas and still lack connection between this issue and the reality of the student. Football is a very common issue on a daily basis for most of the students of this school, and also a joke among some students and teachers, so a theme motivating learning any math related to it, such as distance between two players positioned on the field, equation of the when a player passes the ball to another, or when kicks the goal, what exactly are the basic issues of analytic geometry of the 3rd grade of high school. The work was done through a football field in reduced size using toy players without necessarily knowing the rules of the game, the idea is that students can visualize distances and even measure to check them. Through a sequence os activities, starting from the concept of distance between two points, gradually lead the student to understand the basic concepts of analytic geometry. One of the main results and related to this project was the participatory learning of students in building their knowledge through experimentation and visualization of concrete linked to the intellectual. The material reached this goal. This work has brought to this author a great professional development since the choice of the theme, its application in the classroom and finally the reflection of everything that has been done and what is recorded in this dissertation.